Perancangan Instalasi Listrik Gedung Polda Manokwari Papua Barat - Susanto, Susanto; Asya'ri, Hasyim, S.T., M.T; Hasan, Umar, S.T., M.T (2016)
Polda Manokwari Papua Barat building is the public service office. Basically, public services related to the broad aspect of life. In the life of the state, the government has the functions to provide the public services which are required the public needed, from regulations services and other services. In order to meet the needs of the people in education, health, utilities, and other. The construction of this building related to the demand of electrical power especially for lighting installation, AC (Air Conditioner), water pump, and the lift to provide the comfortable of building customers. This installation is used for the importance of public service, so it is necessary to get a good installation design that appropriate with the reliable calculation, economical and safety operation. The good installation would help to creat the sense of comfortable, safe and quiet for the building customers. The goal of Installation design as is purpose to produce an electricity installation plan for the Polda Manokwari Papua Barat building using AutoCAD program and to determine the points of lamps by using DIALux application, to knows the total electrical energy, to determine the conductor size and main protection device, and bill of quantity. The results from this design showed the total apparent power (S) needed 718188,118 VA / 718,19 kVA with main protection device MCCB (Moulded Case Circuit Breaker) 3 phase for 1250 A and two main conductor NYFGbY 4 x 300 mm2. The bill of quantity design for electricity installation need Rp.4.413.007.555,-. Keywords: Electricity Installation, Main safety, DIALux, AutoCAD, RAB.